(untitled) (Philological Studies, 2023)
The purpose of this paper is to present part of the lexicographical work of the Institute for the Macedonian Language "Krste Misirkov" – Skopje, on the occasion of its jubilee – 70 years since its foundation. The starting point is the Dictionary of the Macedonian language with Serbocroatian[1] interpretations, which was and remains more than a dictionary. [1] During the period of the SFRY’s existence, the official language was Serbocroatian.